Studies on the Mechanism of Quality Changes in the Honey-Processing of Glycyrrhiza Uralensis Using Neutral Desorption Electrospray Ionization Mass Spectrometry - Ying LIU; Lin-lin YU; Xiao-wei FANG; Huan-wen CHEN; Dong WU (Zhipu Xuebao)
Honey-processed Glycyrrhiza (G.) uralensis has a wide range of pharmacological and medicinal effects. The processing of G. uralensis with honey has been associated with an increase in the content of pharmacologically active components and the enhancement of tonic effects. However, the mechanism underlying quality changes during processing remains unclear, as does the influence of its origin on the quality of honey-processed G. uralensis. In this study, the neutral desorption-extractive electrospray ionization mass spectrometry (ND-EESI-MS) method was used to analyze four honey-processed G. uralensis samples with different processing degrees, including raw G. uralensis (S1), raw G. uralensis mixed with honey (S2), heated (S3), and further processed until it was no longer sticky (S4). The samples were analyzed under positive and negative ion modes using 80% methanol as the extractant to explore the quality formation mechanisms during the processing. Additionally, the quality of honey-processed G. uralensis from six origins, namely Inner Mongolia, Xinjiang, Gansu, Anhui, Guangdong, and Jiangxi was also assessed. Five experimental conditions were optimized, including extractant, extractant flow rate, electrospray voltage, extractant air pressure, and auxiliary air pressure at the samples site. Collision-induced dissociation (CID) experiment was used to determine the target ions. A total of 35 compounds in honey-processed G. uralensis were identified, including 17 compounds of hexanal, serine, proline, valine, octanal, methyl caproate, limonene, carvacrol, methyl salicylate, phenylalanine, arginine, ferulic acid, sinapic acid, ethyl myristate, kaempferol, aromadendrin, and glycycoumarin under positive ion mode, and 18 compounds of salicylic acid, protocatechuic acid, p-hydroxyphenylpropionic acid, gallic acid, caffeic acid, liquiritigenin, formononetin, baicalein, naringenin, acacetin, glabridin, glabrone, glabrol, liquiritin, isovitexin, glycyrrhizic acid, glycyrrhetinic acid and liquiritin apioside under negative ion mode. More importantly, active metabolites increased in abundance and were better detected under positive ion mode, such as flavonoids and triterpenoids. The results showed that principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) based on the MS data can effectively distinguish the four different processing degrees of G. uralensis samples. During honey processing, the contents of glabrol, acacetin, glycycoumarin, and glycyrrhetinic acid continued to accumulate. Similarly, PCA and PLS-DA can distinguish the metabolite profile of honey-processed G. uralensis from six origins. The contents of glycyrrhizic acid, glycyrrhetinic acid, liquiritigenin, and naringenin were higher in honey-processed G. uralensis from Inner Mongolia, indicating its superior quality. This study demonstrates a novel technique, which eliminates the need for sample pretreatment, for the rapid, in situ, non-destructive detection of plant-derived foods and Chinese herbal medicines, providing a comprehensive analysis of quality.